KONSTRUKSI DAKWAH BIL HAL MUHAMMADIYAH DALAM MENGHADAPI KRISTENISASI: STUDI KASUS DI BLULUK LAMONGAN - Achmad Lucky Ferdiansyah; Muhammad Wahid Nur Tualeka; Mahmud Muhsinin (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
This research aims to describe and analyze the social dynamics behind the emergence of the issue of Christianization and how to form the counter of Muhammadiyah through the construction of da'wah bil-things in the face of Christianization to maintain religious identity and social harmony. Using a descriptive qualitative approach with the theory of social construction of Fathers L. Berger and Thomas Luckman, this study examines how the pattern of Christianization that develops in Bluluk, Lamongan and how Muhammadiyah responds to the dynamics of Christianization through da'wah of socially constructed things in the community. The results of this study show that the construction of dawkah bil-hal Muhammadiyah is formed through three general patterns: (1) the pattern of externalization is reflected in da'wah activities which are realized through various social actions, education, and community services that represent Islamic values in real life. (2) the pattern of objectivity is reflected in various social activities institutionalized in charity, such as the establishment of ABA Kindergarten, Al-Azhar Mosque, and TPA. (3) the pattern of internalization that occurs when Islamic values that have been institutionalized through Muhammadiyah's charity business are then instilled and lived by Muhammadiyah citizens. The three patterns interact to form an adaptive and moderate model of da'wah construction in Muhammadiyah as a response to the dynamics of Christianization in a pluralistic society. This research confirms that da'wah bil-hal is a constructive strategy of Muhammadiyah in building social harmony and strengthening the resilience of religious identity in plural areas such as Bluluk, Lamongan.